Leksikon Verba dan Nomina Bahasa Tanjung Pucuk Jambi Kabupaten Tebo Provinsi Jambi dalam Lingkungan Perladangan: Kajian Ekolinguistik - Adliza Adliza; Oktavianus Oktavianus; Fajri Usman (Center of Language and Cultural Studies, 2021)
This research is an ecolinguistic study that examines the verb lexicon and noun Tanjung Pucuk Jambi Language in a farming environment. The purpose of this study is to examine the relationship between the verb lexicon and noun, to determine the lexicon that is still in use and the lexicon that has just emerged in the language of Tanjung Pucuk Jambi Village, Tebo Regency, and Jambi Province with the farming environment. The data used in this study is the language of the village of Tanjung Pucuk Jambi. This research uses a qualitative approach. The method and technique used in data collection is a free and involved method with note-taking. The method used in data analysis is the method of the split method and the equivalent method. The results of the analysis are presented in a descriptive way supplemented with pictures and signs to support the presentation of the results of the analysis. The analysis shows that there are still many lexicon verbs and nouns in the Tanjung Pucuk Jambi language that is still in use today. The relationship between the verb lexicon and the Tanjung Pucuk Jambi language noun is closely related to the socio-cultural life activities of the local community with a farming environment where the local community works daily in farming in the fields. Then there are also some verb lexicons and nouns in the language of Tanjung Pucuk Jambi, which have just emerged because they are doing farming activities in new fields by planting oil palm plantations.